THE LEADERSHIP ROLE OF SCHOOL PRINCIPALS IN FOSTERING THE SOCIAL COMPETENCE (EXCELLENT SERVICE) OF PUBLIC PRIMARY SCHOOL ADMINISTRATIVE STAFF IN SIMPANG KEURAMAT SUB-DISTRICT - Jamaluddin; Iskandar, Iskandar; Rizki, Sari (Fakultas Tarbiyah, IAIN Fattahul Muluk Papua, 2024)
This study aims to determine the leadership role of school principals, the social competence of school administration personnel's excellent service, the supporting factors inhibiting the implementation of excellent service and the inhibiting factors of the principal's leadership role in fostering the social competence of school administration personnel's excellent service in Simpang Keuramat District Primary School. The research method is qualitative. Sample selection obtained 3 principals and 3 school administration personnel. The instruments used are interview guidelines and observation sheets. The results of the data analysis show that the school administration personnel of Public Primary School 1, Public Primary School 3, Public Primary School 7 have carried out their duties in accordance with the standards governing the implementation of their duties in permen no 24 of 2008. The results of observations of the development of school administration personnel for each of Public Primary School 1, Public Primary School 3 and Public Primary School 7 are also still categorised as good. The results of the behavioural assessment of school administration personnel from each of the 2 informant schools based on the observed indicators were also categorised as good. Most of the administrative staff carry out as well as possible and the principal has an important role in fostering administrative staff by providing attention, guidance and training in order to improve the insight of these administrative staff.